Treatment of uterine high-grade endometrial stromal sarcoma with apatinib combined with chemotherapy: A case report. Issue 13 (March 2019) - Zhang, Ying; Chen, Chen; Ren, Meng; Cong, Xiaofeng; Li, Zhi; Yang, Lei
Abstract: Rationale: The standard treatment for uterine high-grade endometrial stromal sarcoma (HGESS) is chemotherapy after surgery. However, the traditional combination chemotherapy has certain limitation, for example, the cancer cells will quickly become resistant to the chemotherapy drugs. Apatinib is a small-molecule antiangiogenic agent which has shown promising therapeutic effect against diverse tumor, but it still remains unknown whether apatinib has an antitumor effect in patients with endometrial stromal sarcoma (ESS). Here, we report a case of pulmonary metastasis from uterine HGESS successfully treated with apatinib combined with chemotherapy. We also review relevant literature discussing treatment of ESS. Patients concerns: A 54-years-old Chinese woman complained of intermittent pain in the waist and abdomen for 4 months. The patient was diagnosed as uterine fibroids before operation. The surgeon performed a total hysterectomy with bilateral salpingo-oophorectomy, resection of peritoneal disseminated lesions, and the pathological examination revealed a HGESS. Diagnosis: Uterine HGESS stage IV with lung metastases. Interventions: The patient underwent surgery, chemotherapy, chemotherapy combined with apatinib, apatinib maintenance therapy, and radioactive particle implantation for lung metastasis. Outcomes: The patient experienced the above interventions and achieved good results. And continue oral apatinib (500 mg daily) as maintenance therapy. It has been 16 months since the initial diagnosis, and the patient is still in follow-up. Lessons: Apatinib combined with chemotherapy and apatinib monotherapy as maintenance therapy could be a new therapeutic strategy for ESS.